Changing Event Categorization in Second Language Users Through Perceptual Learning. Issue 2 (9th October 2019) - Vanek, Norbert
Abstract : This study examined the impact of a second language (L2) on how event phases are categorized. The aim was to test how strong a boost the L2 system provides when learners are trained to classify events in a new way. The targeted linguistic contrast was the grammatical expression of change‐of‐state events in progress, available in English but far less so in Chinese. Advanced Chinese learners of English received categorization training in four conditions: action‐biased, completion‐biased, verbally‐distracted, and with overt L2 encoding. Experiment 1 tested the extent to which learners' first language facilitates event categorization. Experiment 2 compared learning success in L2‐based categorization with and without verbal interference. Experiment 3 measured the benefits of explicit L2 verbalization for L2‐based category learning. The results showed that L2 grammar has a graded impact on learning, categorization with overt verbalization having the highest, followed by categorization in silence, and categorization with verbal interference the lowest, although not significantly reduced. Open Practices: This article has been awarded Open Data, Open Materials, and Preregistered Research Design badges. All data and materials, along with preregistration for research design and analyses, are publicly accessible through the Open Science Framework at https://osf.io/rxe6u/ . The study materials are also publicly available via the IRIS database at https://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science: https://osf.io/tvyxz/wiki . Abstract :